GENETIK JARAYONLARNI O‘QITISHDA INTERFAOL METODLAR (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the role of interactive teaching methods in the instruction of genetic processes, examines their effectiveness in developing students’ knowledge, and highlights the advantages of applying modern pedagogical approaches in studying molecular and genetic mechanisms.